Species difference in the in vitro and in vivo metabolism of amtolmetin guacil - Hotha, Kishore Kumar; Dasari, Vijaya Bharathi; Shaik, Abdul Naveed; Syed, Muzeeb; Shivva, Vittal; Lakshmanarao, Ravindranath Krishnarao; Korlakunta, Jayaveera Narasimhulu; Mullangi, Ramesh (Arzneimittelforschung, 2010)
Tolmetin (TMT, CAS 26171-23-3) is a non-steroidal anti-inflammatory drug (NSAID) indicated for the relief of signs and symptoms of osteoarthritis, rheumatoid arthritis and juvenile rheumatoid arthritis. As TMT causes gastro-intestinal side effects like other NSAIDs, its non-acidic prodrug amtolmetin guacil (AMG, CAS 87344-06-7) was synthesized. AMG has similar NSAID properties like TMT with additional gastroprotective property. The aim of this study was to investigate whether TMT and AMG are differentially metabolised in rat and human plasma (fresh and acidified) and liver microsomes. TMT was found to be stable in all the matrices tested viz., rat and human plasma (fresh and acidified) and liver microsomes. AMG was found to be stable only in acidified rat and human plasma. On the contrary, in fresh human plasma and human liver microsomes AMG was rapidly converted to two metabolites, which were subsequently identified as MED5 and MED5 methyl ester, without yielding any intact TMT. However, in rat fresh plasma and liver microsomes, AMG formed MED5 (predominant) and TMT. To corroborate the in vitro findings, in vivo pharmacokinetics (PK) studies were done following separate dosing of AMG in both rats and humans. In rats, the PK data substantiated that following oral administration of AMG it will be converted to TMT resulting in similar PK parameters observed for TMT when it was administered alone. In humans, however, AMG yields low levels of TMT which substantes the in vitro results. Levels of AMG were not detectable in the plasma. These results confirm the species differences in the in vitro and in vivo metabolism and disposition of AMG. More research work to further explore and understand AMG metabolism in humans is required.
Keywords: Amtolmetin guacil, humans, metabolism, pharmacokinetics, rats; CAS 26171-23-3; CAS 87344-06-7; Non-steroidal anti-inflammatory drugs; Tolmetin